Inequality, Low-Intensity Immigration and Human Capital Formation in the Regions of Chile, 1820-1939 - Jörg Baten; Manuel Llorca-Ja\~na (Center for Economic Studies and ifo Institute (CESifo), 2020)
This article traces inequality and numeracy development in the regions of Chile during the 19th and early 20th century. Inequality, measured with anthropometric methods, was associated with a lower speed of human capital formation. Not all talents received the necessary education to make full use of their talent for the regional economy, especially in the south. However, in its northern regions we find that Chile was relatively equal and numerate during the 19th century, and the south converged somewhat during this period. In addition, we study the correlates of low-intensity immigration in Chile. Regions with a relatively high share of North European migrants developed faster in terms of numeracy.
Keywords: N36; N96; O15; 330; inequality; immigration; human capital; numeracy; regions; Chile